Can Cultured Meat Be an Alternative to Farm Animal Production for a Sustainable and Healthier Lifestyle? - Munteanu, Camelia; Mireşan, Vioara; Răducu, Camelia; Ihuţ, Andrada; Uiuiu, Paul; Pop, Daria; Neacşu, Alexandra; Cenariu, Mihai; Groza, Ioan (Frontiers in Nutrition, 2021)
Producing animal proteins requires large areas of agricultural land and is a major source of greenhouse gases. Cellular agriculture, especially cultured meat, could be a potential alternative for the environment and human health. It enables meat and other agricultural products to be grown from cells in a bioreactor without being taken from farm animals. This paper aims at an interdisciplinary review of literature focusing on potential benefits and risks associated with cultured meat. To achieve this goal, several international databases and governmental projects were thoroughly analyzed using keywords and phrases with specialty terms. This is a growing scientific domain, which has generated a series of debates regarding its potential effects. On the one hand the potential of beneficial effects is the reduction of agricultural land usage, pollution and the improvement of human health. Other authors question if cultured meat could be a sustainable alternative for reducing gas emissions. Interestingly, the energy used for cultured meat could be higher, due to the replacement of some biological functions, by technological processes. For potential effects to turn into results, a realistic understanding of the technology involved and more experimental studies are required.